Does Diffusion Make an Institutionally Contested Practice Legitimate? Shareholder Responses to Downsizing in Japan, 1973–2005. Issue 10 (October 2017) - Jung, Jiwook; Mun, Eunmi
Despite predictions to the contrary, institutionally contested practices are sometimes disseminated broadly. Does diffusion indicate they have achieved legitimacy in the eyes of key constituents? The conventional view regards diffusion as a process of legitimization and suggests that unconventional practices gain legitimacy following diffusion. Building on recent studies that view diffusion as an outcome of political struggle, we instead argue that political contestation ramps up as controversial practices are disseminated, making it difficult for them to gain wide acceptance. Their diffusion threatens the stability of preexisting institutional arrangements, and constituents who remain supportive of the status quo react negatively. We test our argument by examining shareholders' response to downsizing in Japan, a practice that is highly controversial given the deeply entrenched norm of lifetime employment. Our analysis of panel data on 1, 791 Japanese firms between 1973 and 2005 shows that neither domestic financial institutions nor foreign investors responded positively to downsizing as it became broadly disseminated. Domestic financial institutions actually responded in increasingly negative ways in the 1990s, while they did not in the 1970s when downsizing was conducted within the framework of the long-term relationship between Japanese firms and their main banks. These results suggest that the relationship between diffusion and legitimacy can be contingent, in that the diffusion of institutionally contested practices can trigger reactions that differ from those of institutionally supported practices.